2020
DOI: 10.1186/s12889-020-08633-5
|View full text |Cite
|
Sign up to set email alerts
|

The impact on selection of non-alcoholic vs alcoholic drink availability: an online experiment

Abstract: Background: Increasing the availability of healthier food increases its selection and consumption. However, there is an absence of evidence related to alcohol. This study aimed to estimate the impact of increasing the absolute and relative availability of non-alcoholic compared to alcoholic drinks on selection. We also assessed whether effects were modified by cognitive resource. Methods: UK adult weekly alcohol consumers (n = 808) were recruited to an online experiment with a hypothetical drink selection task… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 15 publications
(23 citation statements)
references
References 28 publications
4
19
0
Order By: Relevance
“…The selection of non-alcoholic versus alcoholic drinks was recently investigated by Blackwell et al, 2020. The results suggested that availability interventions to encourage healthier selection, respectively choosing nonalcoholic rather than alcoholic drinks, may be most effective when changing the relative availability of options, i.e., increasing the proportion of non-alcoholic drinks and consequently decreasing the proportion of available alcoholic drinks [ 49 ].…”
Section: Resultsmentioning
confidence: 99%
“…The selection of non-alcoholic versus alcoholic drinks was recently investigated by Blackwell et al, 2020. The results suggested that availability interventions to encourage healthier selection, respectively choosing nonalcoholic rather than alcoholic drinks, may be most effective when changing the relative availability of options, i.e., increasing the proportion of non-alcoholic drinks and consequently decreasing the proportion of available alcoholic drinks [ 49 ].…”
Section: Resultsmentioning
confidence: 99%
“…Online studies have been used in the context of manipulating the availability of healthier (vs. less-healthy) foods and non-alcoholic (vs. alcoholic) drinks [ 10 , 11 ], but not (to our knowledge) for exploring altering the availability of meat vs. meat-free options.…”
Section: Methodsmentioning
confidence: 99%
“…7 In what is, to our knowledge, the only previous study that has examined the potential of such an intervention applied to alcohol, the proportion of participants selecting an alcoholic drink decreased from 74% when one-quarter of the available drinks were non-alcoholic, to 51% when three-quarters were non-alcoholic. 12 However, this study only measured hypothetical and mandatory selection of a single drink from a limited range of eight options. Studies using meaningful outcomes and conducted within more naturalistic contexts that include wider product ranges are necessary to inform the development and implementation of real-world interventions and policies.…”
Section: Introductionmentioning
confidence: 99%